Assessment of different storage conditions for Staphylococcus hyicus survival - Karine Ludwig Takeuti; Mari Lourdes Bernardi; Andrea Micke Moreno; David Emilio Santos Neves de Barcellos (Journal of Infection in Developing Countries)
Introduction: Collecting swabs from skin lesions for bacteriological examination is frequently performed to the diagnosis of exudative epidermitis. This method is fast and non-invasive, but it depends directly on the viability of bacteria in clinical samples, which can be influenced by storage and shipment temperatures and the time of transportation. The aim of this study was to assess the capacity of four commercial transport media and swabs with no transport medium to preserve Staphylococcus hyicus (S. hyicus) for up to 10 days at room temperature and under refrigeration.